TEOLOGI LINGKUNGAN PERSPEKTIF SEYYED HOSSEIN NASR - Maftukhin, M (Jurnal Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2016)
Environmental theology is the science that discusses relationship between religion and nature is primarily concerned with environmental issues. Theology environment is a way to bring God into the ecological aspect. This conception appears as a response to the issue of environmental crises that occurred since the Middle Ages. In the theology perspective, environmental crisis that is currently going on canât be separated from human behavior is conscious or not have damaged the eco system of the earth so that a balance is threatened.This article seeks it by borrowing a concept of Seyyed Hossein Nasr poured in some of his magnum opus. Search of authors for works Nasr, in general the environmental crisis caused by modern human error of viewing the world. Modern humans are greedy and view the world solely as an object of scientific development also caused the loss of esoteric dimension. Nasr then give a solution that is appropriate nature is seen as a theophany; Godâs power mirrors and a haven for humans.Kata Kunci: Teologi Lingkungan, Seyyed Hossein Nasr, Modern